Lars Hällbom; Nitrogenase regulation and ultrastructure of heterocystous cyanobacteria; free living and in lichen symbiosis. - Skjenneberg, Sven (Rangifer, 1982)
Doktoravhandling forsvart i Botanisk auditorium, Uppsala Universitet 19. mai 1982. (Inst. for fysiologisk botanik, Uppsala Universitet).